2000
DOI: 10.1246/cl.2000.146
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Ir for NO-CO Reaction in the Presence of SO2 and Excess Oxygen

Abstract: Catalytic performance of Ir catalysts for reduction of nitric oxide with carbon monoxide in the presence of SO2 and excess oxygen was investigated. NO was selectively reduced with CO on Ir/silicalite in an oxidizing atmosphere containing 1% to 10% O2 in the temperature range of 300-500 °C. The catalytic activity was scarcely influenced by 150 ppm SO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 4 publications
0
43
1
Order By: Relevance
“…Meanwhile, the light-off temperature decreased with an increase of the Ir content. Ogura et al [11] has used Ir/silicalite with an Ir content as low as 0.02% to obtain as high as 30% of CO selectivity. Obviously, our result is consistent with that reported by Ogura et al [11].…”
Section: Effect Of Ir Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the light-off temperature decreased with an increase of the Ir content. Ogura et al [11] has used Ir/silicalite with an Ir content as low as 0.02% to obtain as high as 30% of CO selectivity. Obviously, our result is consistent with that reported by Ogura et al [11].…”
Section: Effect Of Ir Contentmentioning
confidence: 99%
“…Ogura et al [11] has used Ir/silicalite with an Ir content as low as 0.02% to obtain as high as 30% of CO selectivity. Obviously, our result is consistent with that reported by Ogura et al [11]. This behavior of the Ir catalysts suggests that a high content of Ir facilitates the oxidation of CO by O 2 , whilst a lower Ir content benefits for the oxidation of CO by NO.…”
Section: Effect Of Ir Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when the feed gas contained three types of reducing agent, namely CO, H 2 and C 3 H 8 , the enhanced activity of the deNO x process over the Ir/ZSM-5 was evidently due to the reduction of NO by CO or by H 2 . However, it has been reported that under lean conditions, Ir-based catalysts are very active for NO reduction by CO [17], but are inactive by H 2 [23]. In order to make it clear that when a mixture of C 3 H 8 , CO and H 2 was used as the reducing agent, the actual route for NO reduction over the Ir/ZSM-5 is not by H 2 , but by CO, we performed an experiment with a feed containing only CO, and the result is shown in Table 2.…”
Section: Comparison Between Ir/zsm-5 and Cu/zsm-5 Monolithsmentioning
confidence: 99%
“…Moreover, the wider operation window and the higher selectivity to N 2 make it an attractive candidate for the deNO x process under lean conditions. Different from the C 3 H 6 -SCR of NO over Ir-based catalysts, Ogura et al [17] recently reported that Ir/silicalite possessed high catalytic activity for NO-CO reaction in the presence of SO 2 and excess oxygen. This is a very interesting finding because automotive exhaust always contains certain amount of CO.…”
Section: Introductionmentioning
confidence: 99%